Poverty, Somatisation Tendency and Potency in Low-Income Adolescent Groups of India and Israel: Explorations from the Field - Saoni Banerjee; Rachel Lev-Wiesel; Sonali De (MDPI AG, 2023)
Poverty increases vulnerability towards somatisation and influences the sense of mastery and well-being. The present study on adolescents living in relative poverty in a high-income group country (Israel) and a low-middle-income group country (India) explored the nature of somatisation tendency (ST) and its relationship with potency and perception of poverty (PP). Potency, a buffer against stress-induced negative health effects, was hypothesized to be negatively related to ST and mediate the link between PP and ST. Purposive sampling was used to collect questionnaire-based data from community youth (12-16 years) of two metropolitan cities-Kolkata (India, N = 200) and Tel-Aviv (Israel, N = 208). The nature of ST, PP and potency was analysed using descriptive and inferential statistics and correlation-regression statistics and mediation analysis were used to understand the relationship among them. A clinically significant level of ST was reported by both Indian and Israeli youth experiencing 5-7 somatic symptoms on average. Potency was found to be a significant predictor of ST in both countries (p < 0.05) and emerged as a significant mediator (p < 0.001) in the PP and ST relationship among Indian adolescents. The present study highlights potency as a protective buffer in economically vulnerable community adolescents and re-establishes a high prevalence of ST among them, irrespective of their country's global economic position.